Pengaruh Model Pembelajaran Think Pair Share Terhadap Hasil Belajar Matematika Siswa Kelas IV SDN 84 Palembang - anggi, anggicahyakurnia; Ilham Arvan Junaidi; Imelda Ratih Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The background of this study includes low student mathematics learning outcomes, lack of student participation in the learning process, and minimal use of innovative learning methods by teachers. This study aims to evaluate the impact of the Think Pair Share (TPS) learning model on the mathematics learning outcomes of fourth grade students at SDN 84 Palembang, especially on pictogram material. The method used in this study is a quantitative approach with a quasi-experimental design and an unequal control group. The study population consisted of 36 fourth grade students of SDN 84 Palembang, which were divided into two classes: class IVA as the experimental group (19 students) and class IVB as the control group (17 students). Data were collected through observation, documentation, and learning outcome tests including pretest and posttest. Data analysis was carried out by testing normality, homogeneity, and hypothesis testing using the independent sample t-test. The results showed a significant difference between the learning outcomes of students taught with the TPS model and those taught with conventional methods, as seen from the average posttest score of the experimental class which was higher than the control class. Thus, the Think Pair Share learning model is proven to have a positive and significant influence in improving students' mathematics learning outcomes on pictogram material. Keywords: Think Pair Share, learning outcomes, mathematics, pictograms, elementary students.